Surface Area Change Analysis of Kimshung Glacier, Central Himalayas - Dhakal, Bhola Nath (Humanities and Social Sciences Journal, 2024)
This study has analyzed the glacial surface area changes on the Khimsung Glacier in the North-Central Himalayan region of the Bagmati Province of Nepal. This study has used different time series satellite images from the web platform data source i.e. SENTINEL-2 L2A and High-resolution DEM received from the Department of Survey to analyze the change of glacier. Geological and geomorphological maps have been prepared using the ArcGIS Pro software. The data have been assembled from the field visit and published research papers that has been considered to validate the maps. The geomorphological maps have been prepared with stratigraphy data from the field and research papers. The elevation variation map of the glacier has been prepared through digital elevation models (DEM) that have been co-registered with each other. This study has found -0.4 ± 0.1 km²/year from 2017 to 2018 as the rate of change in the surface area of the Khimsung Glacier. Similarly, the coverage area change from 2020 to 2021 has been also observed the same -0.4 ± 0.1 km²/year.